Experimental and theoretical studies of near-ground acoustic radiation propagation in the atmosphere; Proceedings of SPIE; Vol. 10466 : 23rd International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics - Belov V. V. Vladimir Vasiljevich; Burkatovskaya Yu. B. Yuliya Borisovna; Krasnenko N. P. Nikolay Petrovich; Rakov A. S. Aleksandr Sergeevich; Rakov D. S. Denis Sergeevich; Shamanaeva L. G. Lyudmila Grigorjevna (2017, 2017)
Title screen